Comparing biomarker profiles of patients with heart failure: atrial fibrillation vs. sinus rhythm and reduced vs. preserved ejection fraction. (22nd August 2018) - Santema, Bernadet T; Kloosterman, Mariëlle; Van Gelder, Isabelle C; Mordi, Ify; Lang, Chim C; Lam, Carolyn S P; Anker, Stefan D; Cleland, John G; Dickstein, Kenneth; Filippatos, Gerasimos; Van der Harst, Pim; Hillege, Hans L; et al.
Abstract: Aims: The clinical correlates and consequences of atrial fibrillation (AF) might be different between heart failure with reduced vs. preserved ejection fraction (HFrEF vs. HFpEF). Biomarkers may provide insights into underlying pathophysiological mechanisms of AF in these different heart failure (HF) phenotypes. Methods and results: We performed a retrospective analysis of the BIOlogy Study to TAilored Treatment in Chronic Heart Failure (BIOSTAT-CHF), which was an observational cohort. We studied 2152 patients with HFrEF [ejection fraction (EF < 40%)], of which 1419 were in sinus rhythm (SR) and 733 had AF. Another 524 patients with HFpEF (EF ≥50%) were studied, of which 286 in SR and 238 with AF. For the comparison of biomarker profiles, 92 cardiovascular risk markers were measured (Proseek ® Olink Cardiovascular III panel). The circulating risk marker pattern observed in HFrEF was different than the pattern in HFpEF: in HFrEF, AF was associated with higher levels of 77 of 92 (84%) risk markers compared to SR; whereas in HFpEF, many more markers were higher in SR than in AF. Over a median follow-up of 21 months, AF was associated with increased mortality risk [multivariable hazard ratio (HR) of 1.27; 95% confidence interval (CI) 1.09–1.48, P = 0.002]; there was no significant interaction between heart rhythm and EF group on outcome. Conclusion: In patients with HFrEF, the presence of AF was associated with a homogeneously elevated cardiovascular risk marker profile. In contrast, in patients with HFpEF, the presence of AF was associated with a more scattered risk marker profile, suggesting differences in underlying pathophysiological mechanisms of AF in these HF phenotypes.